Left Ventricular Remodeling and Heart Failure Predictors in Acute Myocardial Infarction Patients with Preserved Left Ventricular Ejection Fraction after Successful Percutaneous Intervention in Western Romania - Diana-Aurora Arnautu; Minodora Andor; Bogdan-Flaviu Buz; Mirela-Cleopatra Tomescu; Cristina Vacarescu; Simina Crisan; Dan Gaita; Constantin-Tudor Luca; Dragos Cozma (Life, 2022)
(1) Acute myocardial infarction (AMI) patients are at risk of left ventricular (LV) remodeling and heart failure (HF), even after successful revascularization by percutaneous coronary intervention (PCI). We wanted to assess the independent predictors of these outcomes in AMI patients. (2) Methods: The study enrolled patients with a LVEF ≥50% after a successful PCI for their first AMI. After 24 months, patients were separated into two groups based on whether their LVEF remained ≥50% (group I), or decreased to <50% (group II). (3) Outcomes: 26% of the patients experienced a decrease in LVEF below 50%, 41% showed LV remodeling, and 8% had experienced HF hospitalizations. HF hospitalizations were significantly more frequent in group II patients (p < 0.0001). The Killip class at admission >2, infarct-related longitudinal strain ≤−12.5%, and the presence of LV remodeling were identified as independent predictors of HF hospitalizations. (4) Conclusions: About 26% of AMI patients with normal LV function after a successful PCI developed HF. More sensitive techniques are required that allow for a more efficient risk-stratification and preventive therapy to reduce LV remodeling and HF in AMI patients with LVEF ≥50% after a successful PCI. The detection of abnormal ventricular deformation patterns after PCI by speckle-tracking echocardiography might be a valuable method in this approach.